Comparing the effect of phenytoin cream and aqueous Quercus infectoria gall extract on wound healing in adalt male Wistar rats - arash tavaf; mahdieh raeeszadeh; loghman ekradi (Fasa University of Medical Sciences, 2017)
Background & Objective: Skin is of great significance for protecting body against dehydration, bleeding and invading microorganisms. The wounds are prone to bacterial infections and may increase the possibility of scar formation. The aim of this study was to evaluate the effects of phenytoin cream and aqueous Mazu extract on wound healing in rats. Material & Methods: 30 male Wistar rats weighing 200-180 g were randomly selected and divided into 5 groups. Having created a 2-cm wound in the animal's neck (epidermal and dermal), the researchers administered normal saline (control), phenytoin cream, aqueous extract of Quercus Infectoria Galls to the groups with concentrations of 5%, 25%, and 50%  to heal them for 21 days. On the 3rd, 6th, 9th, 12th, 15th, 18th, and 2st, day the diameter of the wound was measured. On 21st day, wound sampling was carried out and prepared for histopathological studies. Results: Improvement percentage in the group that received 5% aqueous extract was more than other groups and this difference was significant among control groups on the 3rd, 6th, 9th , and 18th day (P<0.05) and among groups that received phenytoin on the 3rd and 6th day (P<0.05. The macroscopic and microscopic results show that the 5% aqueous extract, phenytoin, normal saline, and 25% and 50% extract played the largest role in wound healing respectively. Conclusion: According to its antioxidant and antimicrobial effects, the 5% aqueous extract of Quercus Infectoria Galls can be important in wound healing and even superior to phenytoin.